Teilzeitarbeit im Lebensverlauf von Männern Zur beruflichen Strukturierung von Übergängen und Konsequenzen - Althaber, Agnieszka (Verlag Barbara Budrich, 2022)
The book examines how occupations as contextual factors shape men's part-time transitions. It identifies occupational gender segregation and occupational working time arrangements as central influencing factors. Although part-time work is more common in female-dominated occupations, it is mainly occupational working time arrangements that structure men's part-time transitions. Moreover, part-time work leads to significant career disadvantages for men independently from the occupational contexts.